2013
DOI: 10.1176/appi.ap.11070137
|View full text |Cite
|
Sign up to set email alerts
|

Career Progress in Online and Blended Learning Environments

Abstract: Career-development conferences can support career growth for trainees. Online training provides a cost-effective and time-efficient alternative to in-person methods, while still enhancing key markers of career progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, the use of virtual tools would increase the number of conferences that researchers can attend and, particularly, improve accessibility for remote and poorly funded researchers and students. Because virtual conferencing is relatively new to ecology and conservation, it may be necessary to test a number of formats and evaluate their success relative to attendance and diversity and delegate engagement and satisfaction (DeRosier et al 2013). We examined 4 virtual conference models ( Fig.…”
Section: Next-generation Models For Virtual Conferencingmentioning
confidence: 99%
“…However, the use of virtual tools would increase the number of conferences that researchers can attend and, particularly, improve accessibility for remote and poorly funded researchers and students. Because virtual conferencing is relatively new to ecology and conservation, it may be necessary to test a number of formats and evaluate their success relative to attendance and diversity and delegate engagement and satisfaction (DeRosier et al 2013). We examined 4 virtual conference models ( Fig.…”
Section: Next-generation Models For Virtual Conferencingmentioning
confidence: 99%
“…In career development, authors evaluated the impact of participating in a career development conference for academics in their early-to mid-career. The authors found that participating in the conference led to increased outputs such as publications, research projects, grants, improved collaborations, and presentations (DeRosier et al, 2013). This finding was particularly factual for women.…”
Section: The Impact Of Conferencesmentioning
confidence: 96%